Investigating contributors to performance evaluations in small groups: Task competence, speaking time, physical expressiveness, and likability. - Lucie Nikoleizig (Public Library of Science (PLoS), 2021)
This study compared the impacts of actual individual task competence, speaking time and physical expressiveness as indicators of verbal and nonverbal communication behavior, and likability on performance evaluations in a group task. 164 participants who were assigned to 41 groups first solved a problem individually and later solved it as a team. After the group interaction, participants' performance was evaluated by both their team members and qualified external observers. We found that these performance evaluations were significantly affected not only by task competence but even more by speaking time and nonverbal physical expressiveness. Likability also explained additional variance in performance evaluations. The implications of these findings are discussed for both the people being evaluated and the people doing the evaluating.